Explanation-driven inquiry: Integrating conceptual and epistemic scaffolds for scientific inquiry - Sandoval, William A; Reiser, Brian J (Science education (Salem, Mass.), 2004)
Science education reforms consistently maintain the goal that students develop an understanding of the nature of science, including both the nature of scientific knowledge and methods for making it. This paper articulates a framework for scaffolding epistemic aspects of inquiry that can help students understand inquiry processes in relation to the kinds of knowledge such processes can produce. This framework underlies the design of a technology-supported inquiry curriculum for evolution and natural selection that focuses students on constructing and evaluating scientific explanations for natural phenomena. The design has been refined through cycles of implementation, analysis, and revision that have documented the epistemic practices students engage in during inquiry, indicate ways in which designed tools support students' work, and suggest necessary additional social scaffolds. These findings suggest that epistemic tools can play a unique role in supporting students' inquiry, and a fruitful means for studying students' scientific epistemologies.